2005
DOI: 10.1007/s00595-005-3044-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences in Sex Hormones and Cytokines in Patients Undergoing Major Abdominal Surgery

Abstract: In contrast to the release of pro- and anti-inflammatory cytokines, sex hormones show a gender-specific pattern during the acute phase response 1 week after abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
17
1
1
Order By: Relevance
“…The present study conducted cytokine measurements over a 48-h postoperative period, providing useful initial postsurgical results; however, our knowledge of long-term effects on stress and immune response is limited. During this measurement period, the cytokine levels remained elevated, although previous results suggest a return to baseline levels within approximately 1 week after surgery (26). Our present findings may also be limited by the inability to assess the scope of epidural blockade during the operation.…”
Section: Discussioncontrasting
confidence: 68%
“…The present study conducted cytokine measurements over a 48-h postoperative period, providing useful initial postsurgical results; however, our knowledge of long-term effects on stress and immune response is limited. During this measurement period, the cytokine levels remained elevated, although previous results suggest a return to baseline levels within approximately 1 week after surgery (26). Our present findings may also be limited by the inability to assess the scope of epidural blockade during the operation.…”
Section: Discussioncontrasting
confidence: 68%
“…Available reports also suggest that concentrations of detected CCGFs could vary between males and females. Examples are available predominantly for disease subjects [80][81][82], limited information is available for healthy subjects [83]. Ethnicity and age difference were not considered in this work.…”
Section: Discussionmentioning
confidence: 99%
“…On cellular basis, for example, it was demonstrated that endotoxin tolerance involves the participation of macrophages and, besides others, glucocorticoids [28]; basal IL-6 levels were cyclic in normal menstrual cycle but amounts of IL-6, IL-10, and TNF after stimulation with LPS were not [29]; epinephrine and norepinephrin inhibited IL-6 and TNFα expression in a concentration-dependent manner in monocytes [30]; sex hormones show a gender-specific pattern during the acutephase response 1 week after major abdominal surgery, but ex vivo-stimulated and systemic IL-6, IL-8, IL-10, and TNFα cytokine release was not gender-specific [31]; glucocorticoids inhibited the production of IL-12, IFNÎł, IFNα, and TNFα by antigen-presenting cells and T helper (Th) 1 cells, but upregulated the production of IL-4, IL-10, and IL-13 by Th2 cells, which was a systematically selective suppression of the Th1 cellular immunity axis and a shift toward Th2-mediated humoral immunity, rather than generalized immunosuppression [32]. Some publications report on systemic alterations of cytokine levels following systemic hormone application.…”
Section: Discussionmentioning
confidence: 99%